(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Human dignity is a concept that is often mentioned in core human rights treaties and national constitutions as the foundation of human rights. At its core it demands respect for the life and integrity of the human person, recognition of the equal worth of human beings and respect for their autonomy or self-determination. Many national and supra-national courts also use the concept to explicate the meaning and limitations of human rights. The constitutional court of Germany, South Africa and the European Court on Human Rights are notable in this regard. In recent years, the US Supreme Court has also increasingly used the concept in resolving hard cases and expanding the scope constitutional rights. Though, the role and application of human dignity has received considerable scholarly attention, it is mainly confined to the European constitutional orders and the US constitutional system. With respect to regional human rights systems, scholars have largely focused on examining the role of human dignity in the jurisprudence of European Court of Human Rights and the Inter-American Court. As such, little is known about what role human dignity is playing or could play in the interpretation of rights in the African human rights system. This is alarming considering the poor status of protection of human rights and weak constitutional right jurisprudence in many countries of Africa. Accordingly, this article seeks to fill the lacuna by examining the role of human dignity in the African human rights system by exploring its place in religious and cultural value systems of different African societies.